2012
DOI: 10.5530/ax.2012.2.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of phytochemical constituents in vitro antioxidant activity of Synadium grantii

Abstract: Introduction:In recent years, the search of biologically active compounds from plants has always been of great interest to scientists looking for new sources of useful drugs against infectious diseases. In this present study we investigated quantification of total phenolic, alkaloid content and in vitro antioxidant activity of ethanol (70%), methanol, ethyl acetate and hexane extracts of Synadium grantii. Methods: The quantification of the total phenolic and alkaloid contents were estimated by taking gallic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The findings of the present study are in accordance with those of Dasari et al , which showed that S. grantii has phenolic compounds and the ability to scavenge free radicals [27]. Our findings show that the stem bark of S. grantii had inhibitory activity regarding the myeloperoxidase enzyme and scavenger action against severe oxidants such as O 2…”
Section: Resultssupporting
confidence: 93%
“…The findings of the present study are in accordance with those of Dasari et al , which showed that S. grantii has phenolic compounds and the ability to scavenge free radicals [27]. Our findings show that the stem bark of S. grantii had inhibitory activity regarding the myeloperoxidase enzyme and scavenger action against severe oxidants such as O 2…”
Section: Resultssupporting
confidence: 93%
“…The medicinal properties of plants have been investigated in recent scientific developments throughout the world, due to their potent biological activities and economic viability (Dasari et al, 2012). Several studies describe such biological activities of plants as antibacterial, antifungal, and antiviral.…”
mentioning
confidence: 99%
“…Antioxidant activity is commonly attributed to phenolic compounds, however, spearson correlation analysis revealed a correlation=0.58 (n-12, p=0.048) between alkaloid content and antioxidant activity. Plants from the euphorbiaceae family, such as S. rautanenii have been found to confer antineoplastic activities (Soetan and Aiyelaagbe, 2009), antioxidant activity (Dasari et al, 2012) and this was attributed to the presence of phenolic acids. The phytochemical profile (Table 3) and quantification (Figure 1) suggests that the use of these plants in the traditional setting is rational and may be useful as an anticancer traditional alternative treatment (Wahab et al, 2010).…”
Section: Discussionmentioning
confidence: 99%